Pembentukan Karakter Santri Milenial melalui Model Pengasuhan Berbasis Tontonan Edukasi Islami di Madrasah Ibtidaiyah Nurul Mun’im Pondok Pesantren Nurul Jadid Probolinggo - Faizatul Widat; Fitria Nur Hayati; Muniva Muslimah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2021)
This study aims to describe the character formation of millennial students through a parenting model based on Islamic education spectacles for students at Madrasah Ibtidaiyah Nurul Mun'im Karanganyar Paiton Probolinggo. This research uses a qualitative approach with the type of case study. Analysis of research data using the Miles and Hubarman technique. The results of the study show that the Islamic educative parenting model manifests changes in the character of students who are getting better, such as: increased acts of mutual help, honesty in words and actions, and positive responses to the social environment. The implication of character building through Islamic education shows is one solution for parents and educators who are trying to shape, develop or improve children's character.